Characteristics of Peat Water and Coconut Water Molecules in the Electrolysis Process to Produce Hydrogen Gas - Imron Musthofa; Reza Taufiqi Ivana; Hajar Isworo; Adhiela Noer Syaief; Rusuminto Syahyuniar; Muhammad Rezki Fitri Putra (Logic : Jurnal Rancang Bangun dan Teknologi, 2025)
Hydrogen energy is one of the alternative energies that will help overcome the scarcity of fossil energy. One of the steps to produce hydrogen energy is by the electrolysis method. In this study, the electrolysis process was carried out with a combination of peat water and coconut water. Given that in the South Kalimantan area the existence of peat land is very extensive and there are also many coconut trees. So the main raw materials used can be renewed. In addition, the composition contained in peat water can also help in the electrolysis process which consists of metal minerals such as Na, Mg, Al, Fe, Ca, K, and others. These mineral compounds will also help in accelerating the formation of hydrogen gas. The mineral compounds contained in coconut water and peat indirectly produce electrolyte properties and can be used as catalysts to accelerate the reaction to produce hydrogen gas by the electrolysis method. From the results of the research conducted, as much as 155 ml of hydrogen was produced. Hydrogen gas production, 0.6 A of electric current, and 7.3 Watts of electric power in the 30-minute electrolysis process were found in sample F (1.5 L of pure coconut water). In the electrolysis process, peat water and coconut water, the voltage used during the electrolysis process was 12 V which flowed through the cathode and anode.